2013
DOI: 10.3390/cosmetics1010003
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Surfactants: Promising Ingredients of Cosmetics and Toiletries

Abstract: Surfactants are an essential ingredient for cosmetic, toiletries and personal care products for enhancing their performance. Dimeric surfactants demonstrate superiority compared to conventional surfactants in all areas of application. Dimeric surfactants are extremely promising for utilization in various cosmetic formulations viz. shampoo, lotions, creams, conditioners etc. These surfactants possess extremely unique surface properties viz. lower surface tension, unique micellization, low critical micelle conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…For the same reasons, surfactants are among the most often investigated compounds (Cardoso et al, ; Chen, Xie, Li, & Yu, ; He, Sheng, Li, & Song, ; He, Wang, Chen, Tang, & Feng, ; Hegazy, Rashwan, Kamel, & El Kotb, ; Hordyjewicz‐Baran et al, ; Nesterenko, Drelich, Lu, Clausse, & Pezron, ; Sheng, Li, Zhou, & Song, ). One of the main important attributes of cationic surfactants is their significant antimicrobial activity (Abe & Matsuki, ; Birnie, Roger, & Schnaare, ; Caillier et al, ; Colomer et al, ; Gilbert, ; Kumar & Tyagi, ; Kuperkar, Modi, & Patel, ; Tewfik, ; Tiecco, Cardinali, Roscini, Germani, & Corte, ; Tyagi & Tyagi, ; Zhang et al, ), because of which these compounds have found their applications in many biomedical products. Well‐known quaternary ammonium salts, classic cationic surfactants, exhibit good antibacterial and antifungal properties and are applied, e.g., in domestic and health care, where they are extensively used as disinfectants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reasons, surfactants are among the most often investigated compounds (Cardoso et al, ; Chen, Xie, Li, & Yu, ; He, Sheng, Li, & Song, ; He, Wang, Chen, Tang, & Feng, ; Hegazy, Rashwan, Kamel, & El Kotb, ; Hordyjewicz‐Baran et al, ; Nesterenko, Drelich, Lu, Clausse, & Pezron, ; Sheng, Li, Zhou, & Song, ). One of the main important attributes of cationic surfactants is their significant antimicrobial activity (Abe & Matsuki, ; Birnie, Roger, & Schnaare, ; Caillier et al, ; Colomer et al, ; Gilbert, ; Kumar & Tyagi, ; Kuperkar, Modi, & Patel, ; Tewfik, ; Tiecco, Cardinali, Roscini, Germani, & Corte, ; Tyagi & Tyagi, ; Zhang et al, ), because of which these compounds have found their applications in many biomedical products. Well‐known quaternary ammonium salts, classic cationic surfactants, exhibit good antibacterial and antifungal properties and are applied, e.g., in domestic and health care, where they are extensively used as disinfectants.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus , Pseudomonas aeruginosa , and Candida albicans belong to a particularly problematic group of strains that are causal agents of opportunistic infection. For that reason, the investigations concentrate on searching for a new group of surfactants that show potential antimicrobial activity and that verify and clarify the antimicrobial ability of the compounds obtained (Abe & Matsuki, ; Birnie et al, ; Caillier et al, ; Colomer et al, ; Gilbert, ; Kumar & Tyagi, ; Kuperkar et al, ; Tewfik, ; Tiecco et al, ; Tyagi & Tyagi, ; Zhang et al, ). A relatively new and promising group of surfactants is gemini (dimeric) surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants find applications in almost every industry such as detergents, paints, dye-stuff cosmetics, pharmaceuticals, pesticides, plastics, food, agriculture, asphalt, fuel [1]. Amongst all the categories of surfactants, anionic surfactants find wider applications in many fields including pharmaceuticals [2], biotechnology [3], chemical biology [4], and in cosmetics [5] due to their favorable physicochemical characteristics. For example, anionic surfactants can change the surface characteristics of solids by adsorption, in addition enhance the solubility of sparingly soluble compounds in water [6] and can reduce resistance to mass transfer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gemini surfactants are used in numerous fields, such as detergents and cleaning products, cosmetics and toiletries etc. due to good water solubility, low CMC, better wetting ability, foaming, aggregation and rheological properties as well as excellent surface activity in aqueous solution as compared to single chain conventional surfactants [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%